Clinical Guideline Highlights for the Hospitalist: Initial Management of Acute Pancreatitis in the Hospitalized Adult. Issue 12 (23rd October 2019) - Jenkins, Ashley; Shapiro, Jordan
Abstract : GUIDELINE TITLE: 2018 American Gastroenterological Association (AGA) Institute Guideline on Initial Management of Acute Pancreatitis RELEASE DATE: March 2018 PRIOR VERSION: Not applicable DEVELOPER: AGA Clinical Practice Guideline Committee FUNDING SOURCE: AGA Institute TARGET POPULATION: Patients within first 48‐72 hours of admission with acute pancreatitis (AP)